2023
DOI: 10.1101/2023.07.03.547492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymodal sensory perception of mechanical and chemical cues drives robust settlement and metamorphosis of a marine pre-vertebrate zooplanktonic larva

Jorgen Hoyer,
Kushal Kolar,
Athira Athira
et al.

Abstract: The Earth's oceans brim with an incredible diversity of microscopic planktonic animals, many of which correspond to the transient larval stage in the life cycles of benthic marine organisms. The mechanisms by which marine larvae use their nervous system to sense and process diverse environmental cues (physical and chemical) in the water column and the benthos to settle and metamorphose is a major problem across the fields of neuroscience, development, evolution and ecology, yet they remain largely unclear. Her… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 116 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…The requirement of Vamp1/2/3 for papilla neuron-mediated tail retraction is not surprising, given its central role in synaptic transmission. Recent studies have demonstrated that mechanosensory papilla neuron activity is necessary for tail retraction and metamorphosis in Ciona ( Hoyer et al, 2023 preprint; Sakamoto et al, 2022 ; Wakai et al, 2021 ). While the papilla neurons are glutamatergic, additional neurotransmitters have been implicated in metamorphosis, including noradrenaline ( Kimura et al, 2003 ), GABA, and gonadotropin-releasing hormone ( Hozumi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of Vamp1/2/3 for papilla neuron-mediated tail retraction is not surprising, given its central role in synaptic transmission. Recent studies have demonstrated that mechanosensory papilla neuron activity is necessary for tail retraction and metamorphosis in Ciona ( Hoyer et al, 2023 preprint; Sakamoto et al, 2022 ; Wakai et al, 2021 ). While the papilla neurons are glutamatergic, additional neurotransmitters have been implicated in metamorphosis, including noradrenaline ( Kimura et al, 2003 ), GABA, and gonadotropin-releasing hormone ( Hozumi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides adhesion, a key role of the papilla is to act as an organ for bimodal mechano- and chemo-sensation regulating larval settlement and metamorphosis [ 75 ]. It has been proposed that the papilla territory may be a homolog of the olfactory placode, based on the expression of several regulators investigated in this study including Sp6/7/8 , Islet , Foxc , and Foxg [ 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%